Compensation of Technological Error During Thread Cutting (Texas Journal of Engineering and Technology, 2022)
The article covers one of the factors affecting the processing kinematic threads procedure and contributing to decrease in the error in the manufacture of threads - the size of the removed allowance. Generally, we will focus on allowance for the final processing, where all accuracy parameters must be complied.